FLORA DAS FLORESTAS ESTACIONAIS SEMIDECIDUAIS DO ESTADO DE MATO GROSSO DO SUL - MOYSES, Debora Gomes; BUENO, Marcelo Leandro; FARIAS, Ivan Justino; VIEIRA, Eliane; PONTARA, Vanessa (ANAIS DO ENIC, 2024)
-